2011
DOI: 10.1021/ol2006538
|View full text |Cite
|
Sign up to set email alerts
|

On the Role of CO2 in NHC-Catalyzed Oxidation of Aldehydes

Abstract: NHC-catalyzed oxidations using carbon dioxide as the stoichiometric oxidant have been carefully investigated. These studies support a secondary role of CO2 in suppressing side reactions and exogenous oxygen as the actual oxidant.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
43
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 108 publications
(45 citation statements)
references
References 39 publications
(51 reference statements)
0
43
0
Order By: Relevance
“…78 Kojic acid derivative 20 proved again to be a good substrate for the coupling with both aliphatic and aromatic enals (regardless of the substitution) in this oxidative method. However, we noted the decrease in percent conversion in the absence of base.…”
Section: Resultsmentioning
confidence: 84%
“…78 Kojic acid derivative 20 proved again to be a good substrate for the coupling with both aliphatic and aromatic enals (regardless of the substitution) in this oxidative method. However, we noted the decrease in percent conversion in the absence of base.…”
Section: Resultsmentioning
confidence: 84%
“…As mentioned above, the major side product identified in these oxidative esterifications was the acid, [19][20][21] Notably, with aliphatic aldehydes this route was the major reaction pathway. It seems that whereas Breslow intermediates derived from aromatic aldehydes are efficiently oxidized by the Ru catalyst, the aliphatic congeners are not readily oxidized with the metal catalyst and reactions mainly occur via O 2 oxidation to eventually provide the corresponding acids.…”
Section: Entrymentioning
confidence: 99%
“…[17] To the best of our knowledge, only one paper describing an NHC-catalyzed esterification between aldehydes and aliphatic alcohols with air as the terminal oxidant showing very limited substrate scope was published. [19,20,21] However, these oxidations do not necessarily need to proceed via acylazolium ions. Importantly, NHC-catalyzed oxidation of aldehydes to the corresponding acids with air as the terminal oxidant is documented.…”
Section: Introductionmentioning
confidence: 99%
“…An interesting conversion of aromatic aldehydes to acids with 15 mol % of an NHC-salt, DBU and CO 2 has been reported by Nair et al [24]. However Bode et al recently concluded that oxygen is the oxidant in these reactions [25]. An oxidative carboxylation of activated arylaldehydes with 10% water in DMF by 5 mol % of a sulfoxylalkyl-substituted NHC has been described by Yoshida et al [26].…”
Section: Resultsmentioning
confidence: 99%